The relationship between planned change and successful implementation of computer-assisted instruction (CAI) within higher education in nursing as perceived by faculty. - Perciful EG (Relationship Between Planned Change & Successful Implementation of Computer-assisted Instruction (cai) Within Higher Education in Nursing as Perceived by Faculty, 1990)
The purposes of this ex post facto correlational study were to: (a) examine planning for the implementation of computer-assisted instruction and (b) develop reliable and valid instruments to measure the degree of planned change and successful implementation of CAI. Lewin's concept of planned change, derived from field theory, provided the theoretical framework. The purposively selected sample consisted of 77 NLN-accredited baccalaureate nursing programs which had received grant money from the Helene Fuld Health Trust to implement computer technology. The sample represented 35 states across the United States. Data were provided by nurse faculty (N = 278) from the 77 schools in the sample. The mail survey utilized a questionnaire composed of three instruments and a demographics section. The three instruments included the Planning and Implementing Phases for CAI (PIP-CAI), the Successful Implementation of CAI (SI-CAI), and the Attitude Toward CAI, a Semantic Differential Tool. A content validity index of.81 for the PIP-CAI and,.79 for the SI-CAI was established by a panel of experts in computers and nursing. Cronbach's reliability coefficient for internal consistency for the PIP-CAI was.91. Both the SI-CAI and the Attitude Toward CAI had alpha coefficients of.88. Two hypotheses were tested in this study. The first hypothesis predicted a relationship between planned change and successful implementation of CAI and was supported (r =.86, p < .001). The second hypothesis, which predicted that the eight factors in planned change would account for more of the variance in successful implementation of CAI than any one factor, was partially supported. The findings of this study have the potential to assist nurse educators and those who award grant money for CAI use to better predict success with the implementation of CAI, add to a developing theory base for the science of nursing education, and provide instruments to measure planning for CAI and successful implementation of CAI. (Scientific symbols modified where possible in accordance with CINAHL policy.)